Mediatization, Spatial Coherence and Social Sustainability: The Role of Digital Media Networks in a Swedish Countryside Community - Jansson, André (Culture Unbound, 2010)
What does the implementation of new communication networks mean for the spatial coherence and social sustainability of rural communities? This paper takes its key from Wittel’s discussion of network sociality, understood as the opposite of Gemeinschaft. Wittel’s argument may inform our understanding of how communicative patterns in rural communities are partly reembedded through ongoing media transitions. But it must also be problematized. Relating Wittel’s discussion to Halfacree’s model of spatial coherence and Urry’s notion of network capital, as well as to findings from an ethnographic study in a Swedish countryside community, a more complex view is presented. It is argued that global communication networks under rural conditions contribute to the integration and sustainability of the community, as much as to processes of expansion and differentiation. The results show that network sociality and community constitute interdependent concepts. Through their capacity of linking people to external realms of interest, while simultaneously reinforcing their sense of belonging in the local community, online media promote ontological security at the individual level, thus operating as a social stabilizer.